ELOVL2: Not just a biomarker of aging - Chao, Daniel L. (Transl Med Aging, 2020)
DNA methylation of the ELOVL2 (Elongation Of Very Long Chain Fatty Acids-Like 2) promoter is one of the most robust molecular biomarkers for chronological age, but whether ELOVL2 plays a functional role in aging has not been explored. ELOVL2 encodes a transmembrane protein involved in the synthesis of very long polyunsaturated fatty acids (VLC-PUFAs). These fatty acids play important roles in retinal biology and photoreceptor renewal, key processes implicated in age-related eye diseases such as age-related macular degeneration (AMD). Here, we summarize our work deciphering the role of ELOVL2 in the eye emphasizing the potential functional role of age-related DNA methylation in the pathophysiology of AMD.